APPLICATION OF AN INTERVENTION PROGRAM FOR THE BENEFIT OF PHYSICAL AND EMOTIONAL HEALTH IN ELDERLY ADULTS OF FEMALE SEX OF HERMOSILLO, SONORA - Chávez Valenzuela, María Elena (2018)
A quantitative study of a quasi-experimental design was conducted to identify the physical and emotional benefits promoted by a systematized physical activation program in older women of the National Institute for Older Persons and the Institute of Worker Safety and Social Services of the State of Sonora. The Senior Fitness Test (SFT) and the Goldberg Anxiety and Depression Scale (GADS) were applied to a non-probabilistic sample of 70 women over 65 years old (M = 68.4, SD = 5.12 years) from Hermosillo, Sonora. The results showed a decrease of 61% in the prevalence of anxiety and a 30% decrease in the symptom of depression after the program. Statistically significant changes were observed in the muscular flexibility of the lower extremities (p <0.05). Regarding aerobic resistance, the participants managed to increase an average of 36 meters more than they had traveled in the six minutes of walking at the beginning of the program. The program of physical activity systematized in older women reduces the prevalence of anxiety and depression and develops the ability to stretch, aerobic capacity, agility, and dynamic equilibrium.